The effect of mouth breathing on SNA angle and maxillary arch dimensions (Mustansiria Dental Journal, 2005)
Mouth breathing is associated with many dental and facial problems andthought of as having a bad effect on orthodontic treatment .The aim of this study was to study the effect of mouth breathing on SNA anglemaxillary incisor to SN angle and dental arch dimensions. And to compare thesevalues with those of nasal breathers. A study sample of 17 mouth breathers werecompared with 17 nasal breathers. Results showed for the mouth breather's very smallincrease in SNA angle with marked proclination of upper incisors, and constriction ofupper arch which is more in the posterior segment .